Implications of CYP21A2 gene duplications in carrier screening and prenatal diagnosis of congenital adrenal hyperplasia due to 21 Hydroxylase deficiency - Sudhisha Dubey; Renu Saxena; Ratna Dua Puri; Ishwar Chander Verma (Indian Pediatrics Case Reports, 2022)
Background: Congenital adrenal hyperplasia (CAH) is an autosomal recessive disorder that presents as salt wasting or simple virilization (SV). It is due to biallelic mutations in the CYP21A2 gene that encodes the 21-hydroxylase enzyme. This gene is susceptible to deletions and duplications due to the presence of a homologous pseudogene and its location in the RCCX module. This complicates the interpretation of molecular analysis of the CYP21A2 gene. Clinical Description: During preconception counseling and subsequent workup of a couple, the wife (who had been diagnosed with simple virilizing CAH at the age of 14 years, based on clinical and metabolic profile) was identified with c.373C >T variant on one and a deletion on the other allele of CYP21A2. Her asymptomatic husband harbored a novel c. 939+5G>A variant in intron 7 of CYP21A2. Prenatal diagnosis by Sanger sequencing revealed the presence of both maternal (c.373C>T) and paternal (c. 939+5G>A) variants in the fetus, indicative of SV form. After genetic counseling, the parents decided to continue with the pregnancy. Management and Outcome: A baby boy was born who underwent investigations according to the standard protocol. However, a diagnosis of CAH could not be established conclusively. The molecular diagnosis of both baby and parents was revisited. It was found that the baby harbored a duplication of CYP21A2 (inherited from his father) along with a novel variant. The duplication neutralized the paternal variant, and thus the baby was not affected, but a carrier. Conclusion: Evaluation of duplication in parents is crucial before prenatal testing, as duplications have important bearing on the carrier status.